Collected works - Bohr, Niels, 1885-1962 (North-Holland Pub. Co., 1972)
The influence of Niels Bohr's work, of his approach to research, both practical and theoretical, is widely felt today. His contributions to our knowledge of the atomic constituents of matter and to our view of science, remain of fundamental importance. The publication of his collected works will give historians of science and scientists easy access to a life-work entirely devoted to the rational analysis of the laws of nature and of the singular character of their meaning for us. In addition to Bohr's published papers, the series includes unpublished manuscripts and a wide selection of letters and other documents, with explanatory notes.